Culture density of menstrual blood-derived stromal/stem cells determines the quality of T cell responses: An experimental study - Shohreh Nikoo; Massoumeh Ebtekar; Mahmood Jeddi-Tehrani; Mahmood Bozorgmehr; Amir-Hassan Zarnani (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Menstrual blood-derived stromal/stem cells (MenSCs) are a new population of refreshing and highly proliferative stem cells. Immunomodulatory effects of MenSCs profoundly depend on their relative density. Objective: To find whether MenSCs cultured at varying numbers would differentially affect the allogenic peripheral blood mononuclear cells (PBMCs) key features. Materials and Methods: PBMCs were co-cultured with various MenSCs numbers. PBMCs proliferation was investigated via 3 H-thymidine incorporation. Flow cytometry was used to assess human leukocyte antigen (HLA)-DR, HLA-ABC, HLA-G, and co-stimulatory markers on MenSCs and the percentage of regulatory T cells (Tregs) among PBMCs. The concentration of cytokines was determined in supernatant of co-cultures. Results: The support of PBMCs proliferation at low MenSCs densities correlated with higher levels of pro-inflammatory interferon gamma (IFN-γ) in MenSCs/PBMCs co-culture and increased expression of HLA-DR by MenSCs. On the other hand, the suppressive property of MenSCs at higher densities was independent of Treg frequency, but correlated with a high concentration of Interleukin (IL)-6 and IL-10 in the co-cultures. Conclusion: Totally, at different seeding densities, MenSCs could differentially interact with PBMCs leading to significant changes in the level of anti- and/or pro-inflammatory factors. These preliminary in vitro results are suggested to be taken into consideration in experimental models of MenSC-based immunomodulation. Nonetheless, for efficient utilization of MenSCs anti-inflammatory features in pre-clinical disease models, we still need to broaden our knowledge on MenSC-immune system cross-talk; this could play a part in designing more optimized MenSCs injection modalities in the case of future pre-clinical and subsequently clinical settings.Key words: Menstrual, Stromal cells, T cell response, Interferon- γ , Regulatory T cells, Cytokines.